Monitoring and identification of mycotoxins in marketed bakery bread during monsoon - GAJENDRA PRASAD, ASHOK KUMAR SINHA and (Indian Phytopathology, 2002)
A survey of marke.ed bread during monsoon revealed infestation with mycotoxigenic fungi viz. Aspergillusflavus group producing aflatoxins, A. ochraceus producing ochratoxin-A and Penicillium spp. Producing citrinin in liquid culture. Of the 76 bread samples obtained from bakery and markets in towns and villages, 16 were contaminated by mycotoxins. Aflatoxins were the most common mycotoxin detected either alone or with citrinin as eo-contaminant,